Electric Circuit Analysis using Finite Element Modeling - Sveikata, J.; Tarvydas, P.; Noreika, A. (Elektronika ir Elektrotechnika, 2005)
Problem of electric circuit modeling by finite element modeling is investigated. Possibilities of application of graphical redactor implemented in ANSYS/Emag environment and intended to form electric circuits are analyzed. Characteristics of finite elements CIRCU124 and CIRCU125, which are used to model various electronics elements and current and voltage sources, are presented in this paper. Example of electric circuit modeling is presented, in which AM modulator modeling is performed. Modeling consists of two stages – first, signal characteristic is calculated using its analytical expression , and later the same signal is modeled in ANSYS/Emag environment. Ill. 8, bibl. 7 (in English; summaries in Lithuanian, English and Russian).